(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Listeria monocytogenes (L. monocytogenes) is a Gram-positive, facultative intracellular bacterial pathogen that can cause a severe invasive disease (listeriosis), mainly in immunocompromised, elderly individuals, and pregnant women, characterized by sepsis, neonates and miscarriage. Objective: To evaluate the association of listeria monocytogenes in abortion in a group of Iraqi women. Methods: A cross-sectional study was designed and included 250 placenta tissues obtained from aborted women, each placenta sample was divided into two parts each about 50 gm in weight, one stored in 10% formaldehyde solution to use for histopathological study using Hematoxylin and Eosin (H&E) staining procedure, while the second part cut into small pieces about 15 gm and washed and stored in 5 ml normal saline solution 0.85% to use in detection of the presence of the bacterium using conventional bacteriological methods. Results: Out of 425 placenta samples only 250 were diagnosed to be placentitis and only 15 isolates of L. monocytogenes were isolated and constitutes 6% of the total number of placentitis. Distribution of placentitis due to listeria and age groups have been shown no statistical significant differences (P = 0.099). Also, there was no statistical significance difference between the percentage of isolated L. monocytogenes and the time of gestation in aborted women with placentitis (P value was 0.689), and also no significance in association between number of abortion and isolation of L. monocytogenes (P = 0.689). Conclusion: No association between L. monocytogenes and recurrent abortion or with time of gestation or the age of the patients. Keywords: Listeria monocytogenes, placenta, aborted women Citation: Qassim KW, AL Attraqchi AAF, Khatab YI. Detection of Listeria monocytogenes in placenta of aborted women. Iraqi JMS. 2017; Vol. 15(4). 404-410. doi: 10.22578/IJMS.15.4.11